Penerapan Sistem Manajemen Keselamatan (SMS) di Bandar Udara Sepinggan Balikpapan - M. N. Nurrasmajid (Research and Development Agency of The Ministry of Transportation, 2011)
Safety is the top priority and must be provided in every flight activity. All institutions that conduct activities in the airport shall have the commitment in implementing Safety Management System, in accordance with national and international standards. In its implementation, Safety Management System consists of 5 (five) indicators i.e. safety policy and objective indicator, danger identification and safety risk management indicator, safety assurance indicator, safety promotion indicator, and emergency response planning indicator. The operators of Sepinggan Internatinal Airport Balikpapan have implemented almost all 5 (five) indicators and its variables. However, there are no SMS organization and manager safety/officer provided. Only working groups (Pokja) are available. Therefore, reports on events are not documented as materials for analysis which can be useful for avoiding errors to occur again.